2000
DOI: 10.1590/s1517-83822000000100015
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of acetonitrile by cells of Candida guilliermondii UFMG-Y65 immobilized in alginate, kappa-carrageenan and citric pectin

Abstract: Different encapsulation matrices were tested for immobilized cells of Candida guilliermondii UFMG-Y65 used for acetonitrile degradation. Acetonitrile degradation by free cells and cells immobilized in Ba-alginate, κ-carrageenan and citric pectin was studied. The rate of acetonitrile degradation was monitored for 120 h by measuring yeast growth and ammonia concentration. Different alginate concentrations did not affect cell viability, but the period of incubation in BaCl 2 solution reduced the number of viable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Some yeast cultures have the capacity to use nitriles as nitrogen sources (9). Studies on yeast immobilization for nitrile degradation have been made (3,4), but this work is the first to report on a yeast able to use nitrile at high concentrations as its sole nitrogen and carbon source. Uma linhagem de levedura identificada como Geotrichum sp.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Some yeast cultures have the capacity to use nitriles as nitrogen sources (9). Studies on yeast immobilization for nitrile degradation have been made (3,4), but this work is the first to report on a yeast able to use nitrile at high concentrations as its sole nitrogen and carbon source. Uma linhagem de levedura identificada como Geotrichum sp.…”
Section: Resultsmentioning
confidence: 96%
“…Few studies have been carried out on the use of nitriles by yeasts (2,3,4,9,12). All these studies reported the use of nitriles and corresponding amides as the only nitrogen source.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the bioconversions of nitriles have been carried out using free cells and little information is available on the use of immobilized microbes for transformation of nitriles (Dias et al, 2000b ;Takagi et al, 1994 ;Nawaz et al, 1993 ). Among the various methods available for immobilization of cells (Chibata, 1978 ), yeasts have been immobilized by entrapment in alginate, κ-carageenan and citric pectin (Dias et al, 2000b ).…”
Section: Biotransformation Of Nitriles and Amides With Immobilized Cementioning
confidence: 99%
“…Most of the bioconversions of nitriles have been carried out using free cells and little information is available on the use of immobilized microbes for transformation of nitriles (Dias et al, 2000b ;Takagi et al, 1994 ;Nawaz et al, 1993 ). Among the various methods available for immobilization of cells (Chibata, 1978 ), yeasts have been immobilized by entrapment in alginate, κ-carageenan and citric pectin (Dias et al, 2000b ). Alginate immobilized cells of Candida guilliermondii UMFG-Y65, degraded acetonitrile more efficiently than κ-carrageenan or citric pectin immobilized cells (Dias et al, 2000b ).Since calcium alginate beads are unstable in phosphate buffer (commonly used buffer in reactions comprising bioconversion of nitriles), barium chloride has been employed for cross-linking of alginate to provide better stability to the resultant beads during biotransformation reaction (Dias et al, 2001a ).…”
Section: Biotransformation Of Nitriles and Amides With Immobilized Cementioning
confidence: 99%
See 1 more Smart Citation